MERGERS, TAKE OVER AND STRATEGIC ALLIANCES IN THE WORLD AND POLISH ECONOMY - Kraciuk, Jakub (Acta Scientiarum Polonorum. Oeconomia, 2003)
The article presents one aspect of globalisation, namely capital concentration processes in the world and in Poland. Three different ways of the concentration are characterised: mergers, take over and strategic alliances, as well as the ways of enterprises consolidation in our country are presented.